2017
DOI: 10.1016/j.dark.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Searching for galactic axions through magnetized media: The QUAX proposal

Abstract: We present a proposal to search for QCD axions with mass in the 200 µeV range, assuming that they make a dominant component of dark matter. Due to the axion-electron spin coupling, their effect is equivalent to the application of an oscillating rf field with frequency and amplitude fixed by the axion mass and coupling respectively. This equivalent magnetic field would produce spin flips in a magnetic sample placed inside a static magnetic field, which determines the resonant interaction at the Larmor frequency… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
165
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(169 citation statements)
references
References 33 publications
2
165
0
Order By: Relevance
“…Applications of such systems range from quantum information processing [1][2][3] and coherent conversion of microwave to optical frequency light [4,5], to microwave components in the form of filters, circulators, isolators and oscillators. Additionally, such systems are used in the study of hybrid quantum systems [6,7], Quantum electrodynamics (QED) [8][9][10], and direct detection of dark matter [11][12][13][14][15]. In the context of dark matter detection, it has been shown that strongly coupled cavity-magnon systems are useful for expanding the range of detectable dark matter masses [11].…”
Section: Introductionmentioning
confidence: 99%
“…Applications of such systems range from quantum information processing [1][2][3] and coherent conversion of microwave to optical frequency light [4,5], to microwave components in the form of filters, circulators, isolators and oscillators. Additionally, such systems are used in the study of hybrid quantum systems [6,7], Quantum electrodynamics (QED) [8][9][10], and direct detection of dark matter [11][12][13][14][15]. In the context of dark matter detection, it has been shown that strongly coupled cavity-magnon systems are useful for expanding the range of detectable dark matter masses [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, there are a number of running (ADMX [71], HAYSTAC [88], OR-GAN [89]), presently being assembled (CULTASK [72], QUAX [90]), or planned (ABRA-CADABRA [73], KLASH [91], MADMAX [74], ORPHEUS [92]) axion dark matter experiments, which cover a large portion of the mass range of interest for axion dark matter in the pre-inflationary PQ symmetry scenario in Model 2.1, see figure 12. Furthermore, in the meV mass range of interest for the post-inflationary PQ symmetry breaking scenario, the model can be probed by the presently being build fifth force experiment ARIADNE [75] and the proposed helioscope IAXO [76], cf.…”
Section: Jhep02(2018)103mentioning
confidence: 99%
“…Complementary approaches may prove crucial to determine the fractional amount of axions as DM constituent. For instance, inhomogeneous filled cavities, in which the effective axion field is converted to magnetization oscillations of a ferrimagnet, are under study 21 . In this case, single photon detection is required, and it can be realized by e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is related to the width of the axion kinetic energy distribution in the laboratory frame. If we assume a Maxwellian velocity distribution in the Galactic rest frame and we take as the local dark matter virial velocity, we get , and finally 21 where the merit factor qualifies the axion-microwave linewidth in haloscope experiments.…”
Section: Introductionmentioning
confidence: 99%